Trombiculid mites (Hannemania sp.) in leptodactylus chaquensis (Amphibia: Anura) inhabiting selected soybean and rice agroecosystems of argentina - Attademo, Andres Maximiliano (2012)
Trombiculid mites are known to parasitize a variety of amphibian species; however, few comparisons of mite parasitism among sites have been made. Here, Hannemania sp. parasitism in frogs (Leptodactylus chaquensis) inhabiting agroecosystems from mideastern Argentina was described. A total of 40 adult frogs (22 females and 18 males) were analyzed to detect ectoparasite Hannemania spp. larvae. Prevalence and mean abundance of Hannemania sp. were consistently higher in frogs from the agroecosystems (rice and soybean fields) than from two reference sites. Leptodactylus chaquensis might be considered an important host species of Hannemania sp., particularly in agricultural areas.